THE RELATIONSHIP BETWEEN PARENTING PATTERNS AND LEARNING MOTIVATION OF STUDENTS - Resi Suci Amanda; Nadhea Putri Ramadhani; Aziz Dwi; Muhammad Tripiando (CV. Doki Course and Training, 2023)
The family is the starting place to learn everything in the world, and parents are responsible for their children, which are compassionate, uplifting and nurturing. Every parent has their own parenting style which will affect a child's motivation in doing things, for example studying. Someone who has high motivation to learn will understand the lessons given more quickly, but vice versa, people who have low motivation will find it difficult to accept the learning given by them. In this research using quantitative method withof 19 items from parenting and 20 items from motivation with the sample being UIN Raden Fatah Palembang students